Ireland, the Common Agricultural Policy and the less developed countries - Matthews, Alan (Statistical and Social Inquiry Society of Ireland, 1985)
The price provisions of the Common Agricultural Policy (CAP) are designed to transfer income to European farmers and to maintain a secure supply of food for European consumers. The consequences of this policy for countries outside the European Community (EC) have become increasingly contentious now that the EC has passed the point of self sufficiency for many temperate zone food products and has become a major exporter, with the aid of export subsidies, to world markets. These consequences are of two kinds (a) CAP protection leads to lower prices on world markets for CAP products, though its effect on the prices of substitutes for CAP products (e g oilseeds) is less clear, (b) CAP protection increases the instability of world market prices. EC agricultural protection is usually seen as damaging to the interests of the less developed countries (Valdes and Zietz, 1980, Fitzpatnck, 1982), though more recently there is a growing realisation that many importing LDCs benefit from the availability of cheaper food supplies on the world market (Bale and Koester, 1984, Matthews, 1985). The impact of the CAP on LDCs is of special interest to Ireland, given the importance of the agricultural sector and the role of agricultural exports here. This paper presents the results of some new calculations of the impact of the CAP on LDCs, and discusses their implications for Irish development co operation policy.
Symposium on Ireland, Europe and the Third World
Read before the Society, 28th March 1985
Keywords: Common agricultural policy; International trade; 314.15